2013
DOI: 10.1128/aem.00695-13
|View full text |Cite|
|
Sign up to set email alerts
|

The Microbiome of the Red Sea Coral Stylophora pistillata Is Dominated by Tissue-Associated Endozoicomonas Bacteria

Abstract: bEndozoicomonas bacteria were found highly associated with the coral Stylophora pistillata, and these bacteria are also ubiquitously associated with diverse corals worldwide. Novel Endozoicomonas-specific probes revealed that Endozoicomonas bacteria were abundant in the endodermal tissues of S. pistillata and appear to have an intimate relationship with the coral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
242
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 249 publications
(266 citation statements)
references
References 22 publications
13
242
3
1
Order By: Relevance
“…Endozoicomonas are Gammaproteobacteria frequently observed in reef‐building corals (Bayer et al., 2013; Bourne et al., 2008; Glasl, Herndl, & Frade, 2016; Neave, Michell, et al., 2017; Neave, Rachmawati, et al., 2017; Pantos, Bongaerts, Dennis, Tyson, & Hoegh‐Guldberg, 2015; Pogoreutz, Rädecker, Cárdenas, Gärdes, Wild, et al., 2017) and highly dominant in pocilloporid hosts where they were found to reside deep within the gastrovascular tissues (Bayer et al., 2013; Neave, Rachmawati, et al., 2017). More generally, Endozoicomonas are commonly assumed to provide an important role in coral holobiont functioning due to their widespread prevalence and high abundance in many coral species (Bayer et al., 2013; Gignoux‐Wolfsohn, Aronson, & Vollmer, 2017; Glasl et al., 2016; Jessen et al., 2013; Meyer, Gunasekera, Scott, Paul, & Teplitski, 2016; Neave et al., 2016; Neave, Rachmawati, et al., 2017) and apparent metabolic versatility (Ding, Shiu, Chen, Chiang, & Tang, 2016; Hyun et al., 2014; Neave, Michell, et al., 2017; Yang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endozoicomonas are Gammaproteobacteria frequently observed in reef‐building corals (Bayer et al., 2013; Bourne et al., 2008; Glasl, Herndl, & Frade, 2016; Neave, Michell, et al., 2017; Neave, Rachmawati, et al., 2017; Pantos, Bongaerts, Dennis, Tyson, & Hoegh‐Guldberg, 2015; Pogoreutz, Rädecker, Cárdenas, Gärdes, Wild, et al., 2017) and highly dominant in pocilloporid hosts where they were found to reside deep within the gastrovascular tissues (Bayer et al., 2013; Neave, Rachmawati, et al., 2017). More generally, Endozoicomonas are commonly assumed to provide an important role in coral holobiont functioning due to their widespread prevalence and high abundance in many coral species (Bayer et al., 2013; Gignoux‐Wolfsohn, Aronson, & Vollmer, 2017; Glasl et al., 2016; Jessen et al., 2013; Meyer, Gunasekera, Scott, Paul, & Teplitski, 2016; Neave et al., 2016; Neave, Rachmawati, et al., 2017) and apparent metabolic versatility (Ding, Shiu, Chen, Chiang, & Tang, 2016; Hyun et al., 2014; Neave, Michell, et al., 2017; Yang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, Endozoicomonas are commonly assumed to provide an important role in coral holobiont functioning due to their widespread prevalence and high abundance in many coral species (Bayer et al., 2013; Gignoux‐Wolfsohn, Aronson, & Vollmer, 2017; Glasl et al., 2016; Jessen et al., 2013; Meyer, Gunasekera, Scott, Paul, & Teplitski, 2016; Neave et al., 2016; Neave, Rachmawati, et al., 2017) and apparent metabolic versatility (Ding, Shiu, Chen, Chiang, & Tang, 2016; Hyun et al., 2014; Neave, Michell, et al., 2017; Yang et al., 2010). Further, reductions in the abundance of Endozoicomonas in stressed, diseased, or bleached corals are reported in a number of studies, suggesting that pervasive abundance of Endozoicomonas might be an indicator of habitat suitability (Bourne et al., 2008; Cárdenas et al., 2012; Gignoux‐Wolfsohn et al., 2017; Meyer et al., 2016; Morrow et al., 2014; Roder et al., 2015; Röthig et al., 2016; Ziegler et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Endozoicomonas spp. are found to comprise 70 to 95% of the microbiome in several Red Sea (Stylophora pistillata, Pocillopora damicornis, and Acropora humilis) and Caribbean corals (Porites astreoides [49][50][51][52]). These bacteria have also been shown to live endosymbiotically, forming large aggregations deep within coral tissues (51), potentially playing a role in bacterial communication and structuring via the production of quorum-sensing signaling metabolites and antimicrobial compounds (53).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, coevolution of bacteria and coral has been proposed (Thompson et al, 2015), as it was demonstrated for Endozoicomonas symbionts in corals with contrasting life-history traits and across global scales (Bayer et al, 2013;Neave et al, 2016Neave et al, , 2017. Detailed analysis of these studies revealed fine scale host-Endozoicomonas specific patterns suggesting phylosymbiosis between corals and this bacterial genus.…”
Section: Exaiptasia H2 and Cc7 Strains Only Share A Small Common Micrmentioning
confidence: 99%